Mcgraw-Hill's SAT II chemistry - Evangelist, Thomas A. (New York : McGraw-Hill, 2006)
A guide to preparing for the chemistry portion of the SAT II college entrance exam, featuring topic reviews, test-taking strategies, drills and exercises, and five practice tests.
Young Adult
Keywords: Chemistry -- Examinations, questions, etc; College entrance achievement tests -- United States -- Study guides; SAT (Educational test); Chemistry -- Examinations -- Study guides; Colleges and universities -- Entrance examinations -- Study guides; SAT (Educational test)